1998
DOI: 10.1524/ract.1998.82.special-issue.63
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate Complexation of Neptunyl(VI) Ion

Abstract: The neptunyl(VI) ion in aqueous carbonate system has been investigated by solubility measurements in 0.1 Μ NaC10 4 at 25 ± 0.1 °C in equilibrium with 80% C0 2 /0 2 atmosphere. Neptunium was oxidized and stabilized in hexavalent state in the presence of ozone during the experiment. The solubility limiting solid phase was characterized as Np0 2 C0 3 (s) by X-ray crystallography, UV-Vis-NIR photoacoustic spectroscopy and FT-IR photoacoustic spectroscopy. For this solid phase the solubility product lgiT^iNpOaCO,) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…Therefore, Si are stability constants of the Np(VI) tricarbonate and silicate complexes: we determined using the reference values of dissociation constants of carbonic acid, K 1 = 4.45 0 10 37 and K 2 = 4.69 0 10 311 , and metasilicic acid, K 1 = 2.2 0 10 310 and K 2 = 1.6 0 10 312[9], which were recalculated to the ionic strength of 0.1 by the Davies equation[10]. The b 3 value was taken from[11] (log b 3 = 20.41 at an ionic strength of 0.1). The stability constant of the Np(VI) silicate complex we calculated using measured values of pH and known concentrations of carbonate and silicate ions in the solution.…”
mentioning
confidence: 99%
“…Therefore, Si are stability constants of the Np(VI) tricarbonate and silicate complexes: we determined using the reference values of dissociation constants of carbonic acid, K 1 = 4.45 0 10 37 and K 2 = 4.69 0 10 311 , and metasilicic acid, K 1 = 2.2 0 10 310 and K 2 = 1.6 0 10 312[9], which were recalculated to the ionic strength of 0.1 by the Davies equation[10]. The b 3 value was taken from[11] (log b 3 = 20.41 at an ionic strength of 0.1). The stability constant of the Np(VI) silicate complex we calculated using measured values of pH and known concentrations of carbonate and silicate ions in the solution.…”
mentioning
confidence: 99%
“…1. Solubility data sets in ^ = 0.1 M Perchlorate medium are obtained for U(VI) under 100% CO2 atmosphere, while the Np(VI) data set is obtained from solutions equilibrated with a mixture of 80% COJlWo O2 after passing the gas through an ozonizer [36]. With exception of the Observation that Np(VI) solubilities at lg [COi"] > -8 are slightly lower than the corresponding U(VI) data, no general conclusion can be drawn with respect to characteristic differences in the actinyl(VI) systems by Visual inspection of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Kato et al [36] reported solubility data from three separate vessels. Hence, the data is interpreted by a model function where [Np(VI)],"m,i is the i-th measured total Np(VI) concentration, Ig^COz = -0.0969, the solubility product of the solid phase and y?ion the formation constant of the n-th carbonato species of Np(VI).…”
Section: Analysis Of Np(vi) Datamentioning
confidence: 99%
See 2 more Smart Citations